The Uridine diphosphate (UDP)-glycosyltransferases (UGTs) superfamily: the role in tumor cell metabolism - Liu, Wenyu; Li, Jing; Zhao, Rui; Lu, Yao; Huang, Panpan (Frontiers in Oncology, 2023)
UDP-glycosyltransferases (UGTs), important enzymes in biotransformation, control the levels and distribution of numerous endogenous signaling molecules and the metabolism of a wide range of endogenous and exogenous chemicals. The UGT superfamily in mammals consists of the UGT1, UGT2, UGT3, and UGT8 families. UGTs are rate-limiting enzymes in the glucuronate pathway, and in tumors, they are either overexpressed or underexpressed. Alterations in their metabolism can affect gluconeogenesis and lipid metabolism pathways, leading to alterations in tumor cell metabolism, which affect cancer development and prognosis. Glucuronidation is the most common mammalian conjugation pathway. Most of its reactions are mainly catalyzed by UGT1A, UGT2A and UGT2B. The body excretes UGT-bound small lipophilic molecules through the bile, urine, or feces. UGTs bind a variety of tiny lipophilic molecules to sugars, such as galactose, xylose, acetylglucosamine, glucuronic acid, and glucose, thereby inactivating and making water-soluble substrates, such as carcinogens, medicines, steroids, lipids, fatty acids, and bile acids. This review summarizes the roles of members of the four UGT enzyme families in tumor function , metabolism,and multiple regulatory mechanisms,and its Inhibitors and inducers .The function of UGTs in lipid metabolism, drug metabolism, and hormone metabolism in tumor cells are among the most important topics covered.